Parental tdap boosters and infant pertussis: A case-control study - Quinn, H.; Snelling, Thomas; Habig, A.; Chiu, C.; Spokes, P.; McIntyre, P. (American Academy of Pediatrics, 2014)
Copyright © 2014 by the American Academy of Pediatrics. BACKGROUND: Although recommended for almost a decade, evidence for field effectiveness of vaccinating close adult contacts of newborn infants against pertussis ("cocooning") is lacking. We evaluated the impact of a government-funded cocoon program during a pertussis epidemic in New South Wales, Australia. METHODS: We matched all New South Wales laboratory-confirmed pertussis cases aged < 4 months with onset between April 1, 2009, to March 30, 2011 to controls from the state birth register by date of birth and area of residence. Parental vaccine receipt was by self-report, with a subset verified. Parents were considered "immunized" if vaccinated =4 weeks before case symptom onset. The effectiveness of parental immunization (versus neither vaccinated) was quantified as (1 - odds ratio) × 100%. RESULTS: Case households had fewer immunized mothers (22% vs 32%) or fathers (20% vs 31%) but were more likely to include additional and older children. After adjustment, when both parents met our definition of immunized, risk of pertussis at < 4 months of age was reduced by 51% (95% confidence interval 10% to 73%). Maternal vaccination prepregnancy and an immunized father reduced the risk by 51% (95% confidence interval 0% to 76%). CONCLUSIONS: Timely parental pertussis boosters provided significant protection. Evidence of protection from maternal vaccination prepregnancy is biologically plausible, and more precise data on the magnitude and duration of this is important for future policy recommendations.